2014
DOI: 10.1371/journal.pone.0104475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Appropriate Antimicrobial Therapy for Patients with Severe Sepsis and Septic Shock – A Quality Improvement Study

Abstract: BackgroundThere is ample literature available on the association between both time to antibiotics and appropriateness of antibiotics and clinical outcomes from sepsis. In fact, the current state of debate surrounds the balance to be struck between prompt empirical therapy and care in the choice of appropriate antibiotics (both in terms of the susceptibility of infecting organism and minimizing resistance arising from use of broad-spectrum agents). The objective of this study is to determine sepsis bundle compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 26 publications
4
56
1
4
Order By: Relevance
“…Hospital, and especially ICU-related, infections are more likely to be caused by multidrug-resistant organisms and previous antibiotic use is a risk factor for antibiotic resistance. Misdirected initial antibiotic therapy is associated with poor outcome [2, 3], but there is a paucity of epidemiological data in most low-resourced settings. We recommend empirical antibiotic therapy should cover all expected pathogens and likely resistance patterns (1C) based on locally-acquired epidemiological data as large regional variations exist (ungraded).…”
Section: Results and Recommendations For Management Of Infections In mentioning
confidence: 99%
See 1 more Smart Citation
“…Hospital, and especially ICU-related, infections are more likely to be caused by multidrug-resistant organisms and previous antibiotic use is a risk factor for antibiotic resistance. Misdirected initial antibiotic therapy is associated with poor outcome [2, 3], but there is a paucity of epidemiological data in most low-resourced settings. We recommend empirical antibiotic therapy should cover all expected pathogens and likely resistance patterns (1C) based on locally-acquired epidemiological data as large regional variations exist (ungraded).…”
Section: Results and Recommendations For Management Of Infections In mentioning
confidence: 99%
“…There is weak evidence from resource-limited settings suggesting that timely administration of antibiotics is beneficial [2, 4–6]. Observational data suggest that, in many resource-limited settings, the administration of antibiotics to most patients within 1 h of sepsis or septic shock recognition is feasible.…”
Section: Results and Recommendations For Management Of Infections In mentioning
confidence: 99%
“…Antibiotic resistance is emerging as a serious problem due to inappropriate antibiotic use in both grams negative and gram positive organisms. Appropriate antibiotic administration on admission to the emergency department has been reported to improve the quality of life and survival among the patients [9,10]. In view of the emergence of gram-negative organisms, especially the multidrug resistant strains, there is an urgent requirement for antimicrobial stewardship programs [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…The increased life expectancy of individuals (including those who are immune-compromised) and the surge seen with the utilization of invasive medical interventions are all important contributors to the high incidence of sepsis and its complications. International guidelines highlight the need for early identification of the condition and prompt implementation of the treatment, including antibiotics to reduce the serious consequences [8][9][10][11][12][13]. It has been observed that prompt administration of antibiotics and improve outcomes in patients with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…In logistic regression analyses, non-IAAT was strongly associated with MDR and identified as an independent predictor of hospital mortality. In another retrospective study, a total of 1279 patients with severe sepsis and septic shock were identified; of which 32% had bloodstream infections [14]. In these patients, the administration of appropriate antimicrobial therapy was associated with a decrease in hospital mortality, even after adjustment for other covariates.…”
Section: Appropriate Therapymentioning
confidence: 99%